Arrhythmogenic cardiomyopathy as a myogenic disease: highlights from cardiomyocytes derived from human induced pluripotent stem cells - Reisqs, J. B.; Moreau, A.; Sleiman, Y.; Boutjdir, M.; Richard, S.; Chevalier, P. (Frontiers in Physiology, 2023)
Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiomyopathy, characterized by the replacement of myocardium by fibro-fatty infiltration and cardiomyocyte loss, predisposing to high risk for ventricular arrhythmias. ACM has initially been defined as a desmosomal disease because most of the known variants causing the disease are in genes encoding desmosomal proteins. Studying this pathology is complex, notably because human samples are rare and, when available, illustrates the most advanced stages of the disease. Usual cellular and animal models cannot represent all the hallmarks of the human pathology. In the last decade, human-induced pluripotent stem cells (hiPSC) have been proposed as an innovative human cellular model. The differentiation of hiPSCs into cardiomyocytes (hiPSC-CM) is now well controlled and widely used in many laboratories. This hiPSC-CM model recapitulates critical features of the pathology and enables a cardiomyocyte-centered comprehensive approach of the disease and screening of anti-arrhythmic drugs (AAD) prescribed sometimes empirically to the patient. In this regard, this model provides unique opportunities to explore and develop new therapeutic approaches. The use of hiPSC-CMs will undoubtedly help the development of precision medicine to better cure the patient suffering from ACM. This review aims to summarize the recent advances enabled using hiPSCs in ACM context.